OPTIMIZATION OF OCCUPATIONAL HEALTH AND SAFETY IMPLEMENTATION IN THE LEMURU FISH PROCESSING PROCESS IN THE MODERN INDUSTRY OF JEMBRANA BALI - Nugraha, I Made Aditya; Budiadnyani, I Gusti Ayu; Utari, Siluh Putu Sri Dia; Astiana, Ika; Farida, Iftachul; Cesrany, Mahaldika; Khairunnisa, Anis; Juniarta, I Nyoman; Desnanjaya, I Gusti Made Ngurah (Universitas Mataram, 2025)
The fisheries industry, especially in the processing of lemuru fish, has various work risks that can affect the safety and health of workers. These risks include the use of sharp tools, exposure to chemicals, slippery work environments, and the potential for injury due to intensive production processes. Therefore, the implementation of Occupational Health and Safety (OHS) is a crucial aspect in ensuring a safe, efficient, and productive work environment. However, in practice, there are still various obstacles in the implementation of OHS, such as lack of worker awareness, limited safety facilities, and a less-than-optimal supervision system. This study aims to analyze the implementation of OHS in the processing of lemuru fish at XYZ Company, Jembrana, and to identify obstacles and optimize strategies. The research method used is descriptive qualitative with observation techniques, interviews, and SWOT analysis of OHS policies. The results of the study indicate that the implementation of K3 has been running well through the use of personal protective equipment (PPE), compliance with work procedures, and the implementation of safety standards. To be able to optimize this activity, it can be done through increased training, routine supervision, and the use of IoT-based technology for monitoring the work environment. Computer-based OHS management systems, Virtual Reality (VR) technology for simulation, and automation of high-risk processes with robotics can also be applied to reduce work accidents. Data analysis with machine learning also helps in risk prediction. These implementation strategies can improve work safety, create a safer and more comfortable work environment, and increase the competitiveness of the industry in the global market.